Terra sigillata focese da Gortina: dati preliminari dallo scavo dell’Edificio Sud - Giuliodori, Marzia (Rei Cretariae Romanae Fautorum Acta, 2024)
Phocaean Red Slip Ware constitutes the most widespread fine pottery in Gortina from the late 4th century until the end of production around the mid-7th century. The considerable quantity of this pottery found in the recent excavations of the South Building conducted by the University of Macerata in the area of the Byzantine Houses makes it possible to acquire new data on the circulation of this ceramic class in the Cretan capital and to shed new light on the city's cultural and commercial connections with the neighbouring shore of Asia Minor. In this paper we present preliminary typological data from which there is a clear preponderance of Hayes 3 and 10 dishes in the various known variants. Palm-branches and animal motifs and the usual cross motif are attested among the stamped motifs. The recurrence of the form Hayes 10C in late 7th/early 8th century layers seems to confirm the dating beyond the mid 7th century.